PENERAPAN E-GOVERNMENT PADA DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN BONE (STUDI PADA APLIKASI SISTEM INFORMASI MANAJEMEN KEPENDUDUKAN) - Ulfa, Ulfa; Ferawati, Andi; Mustadir, Mustadir (LPPM Universitas Muhammadiyah Mamuju, 2024)
Implementing E-Government in the current modern era requires prioritizing information technology so that online public services can be more effective and efficient. To implement E-Government in the Bone Regency Population and Civil Registry Service in providing services to the community, you need to pay attention to the elements for implementing E-Government. This research aims to determine the application of E-Government in the Bone Regency Population and Civil Registry Service. using qualitative research methods with descriptive research type. Data collection techniques use observation, interviews and documentation. The data analysis process includes data reduction, data presentation and drawing conclusions. The results of this research show 3 elements in implementing E-Government in the Bone Regency Population and Civil Registration Service, namely: 1). The Support Element is the support and desire of the leadership of the Bone Regency Population and Civil Registry Agency in implementing E-Government and the existence of regulations that support implementing E-Government. 2). Capacity elements include the availability of financial resources originating from the Regional Revenue and Expenditure Budget, the availability of infrastructure resources that support implementing E-Government such as computers, wifi, print and others, and the availability of human resources who have the capacity to implement E-Government or online service to the community. And the 3rd). It is a value element which is a benefit felt by the Population and Civil Registry Service of Bone Regency as providing online services to the community which in implementing E-Government provides a large beneficial impact in terms of effective and efficient service innovation at this time in the Population Service agency. and the Civil Registry of Bone Regency, while the benefits felt by the community as those who receive services are the ease of getting services because they no longer need to come to the office to get services, especially those that are far from the office.